How temptation changes across time: effects of self-efficacy for self-regulated learning and autonomy support. Issue 3 (16th March 2022) - Kim, Yeo-eun; Yu, Shirley L.; Shin, Jongho
Abstract: Students often work on academic tasks in the face of an attractive alternative. In an experimental setting, we examined how students perceive temptation differently across time depending on their self-efficacy for self-regulated learning and autonomy-supportive contexts. Specifically, we focussed on how individual differences in self-efficacy for self-regulated learning interact with different autonomy-supportive contexts (provision of either choice or relevance) to predict students' perceived temptation, affect, and performance across time. Results indicated that students low in self-efficacy for self-regulated learning perceived an increase in temptation across time, while those high in self-efficacy for self-regulated learning perceived a decrease in temptation across time. Moreover, we found that especially for students with low self-efficacy for self-regulated learning, providing choice opportunities or adding relevance to the task predicted lower temptation, higher positive affect, and lower negative affect.